2014
DOI: 10.1007/s00125-014-3467-6
|View full text |Cite
|
Sign up to set email alerts
|

Protection from diabetes-induced atherosclerosis and renal disease by d-carnosine-octylester: effects of early vs late inhibition of advanced glycation end-products in Apoe-null mice

Abstract: These data show that DCO protects mice from diabetes-induced vascular and renal disease and that protection against atherosclerosis is more effectively achieved by early treatment than by late treatment, thus suggesting that early inhibition of AGE formation attenuates progression of macroangiopathy and favours development of more stable lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 36 publications
5
48
0
1
Order By: Relevance
“…The clinical importance becomes apparent when realizing that ACE-inhibitors still are the only medication for diabetic patients with nephropathy in order to delay progression. A very recent study on D-carnosine-octylester (a bioavailable carnosine-derivate) in STZ treated diabetic ApoE-null mice displayed similar findings with reduced renal hypertrophy and albuminuria, but no effect on cholesterol36. As glycemic control remained unaffected in this model, we speculate that at least part of the renoprotection is mediated by carnosine, whereas the insulinotropic effect may be mediated by histamine and β-alanine.…”
Section: Discussionsupporting
confidence: 78%
“…The clinical importance becomes apparent when realizing that ACE-inhibitors still are the only medication for diabetic patients with nephropathy in order to delay progression. A very recent study on D-carnosine-octylester (a bioavailable carnosine-derivate) in STZ treated diabetic ApoE-null mice displayed similar findings with reduced renal hypertrophy and albuminuria, but no effect on cholesterol36. As glycemic control remained unaffected in this model, we speculate that at least part of the renoprotection is mediated by carnosine, whereas the insulinotropic effect may be mediated by histamine and β-alanine.…”
Section: Discussionsupporting
confidence: 78%
“…Oxidative stress, reflected by increased cellular oxidation reactions and decreased reduction reactions (Banerjee and Vats, 2013), has a close relationship with HG-induced vascular injury (Battelli et al , 2014, Menini et al , 2014, Thallas-Bonke et al , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore provide a new mechanism by which carnosine improves the metabolic control in diabetes and protect against the development of complications in diabetes. Even though carnosine shown protective effect in several animal models for complications of diabetes (Pfister et al 2011, Riedl et al 2011, Ansurudeen et al 2012, Yapislar & Aydogan 2012, Brown et al 2014, Peters et al 2014, Menini et al 2015 and strongly suggested to be relevant for diabetes complications in humans (Ahluwalia et al 2011, Kurashige et al 2013) the exact mechanism of action is still unraveled. Here we suggest a potential mechanism by showing that carnosine complexly modulates IGFBP1 by different mechanisms, i.e.…”
Section: Discussionmentioning
confidence: 99%